2022
DOI: 10.1002/vms3.788
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tear glucose levels and their correlation with blood glucose levels in dogs

Abstract: Background No previous studies have quantified tear glucose (TG) levels in dogs or compared changes in TG and blood glucose (BG) concentrations. Objective To quantify TG concentration and evaluate its correlation with BG level in dogs. Methods Twenty repetitive tests were performed in alternate eyes of four dogs, with a minimum washout period of 1 week. Tears and blood were collected at 30‐min intervals with successive glucose injections (1 g/kg) every 30 min. Cross‐correlations of BG and TG levels were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
2
4
0
1
Order By: Relevance
“…4e-(i) shows the representative TG and BG data for a normal beagle subject 1. The BG levels increased rapidly from a baseline of 3.94 mM, which was within the reported normal range for beagles 32 , then reached a maximum value of 16.72 mM at 5 min after the glucose injection. Subsequently, it gradually decreased to 5.67 mM approaching the normal range.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…4e-(i) shows the representative TG and BG data for a normal beagle subject 1. The BG levels increased rapidly from a baseline of 3.94 mM, which was within the reported normal range for beagles 32 , then reached a maximum value of 16.72 mM at 5 min after the glucose injection. Subsequently, it gradually decreased to 5.67 mM approaching the normal range.…”
Section: Resultssupporting
confidence: 81%
“…Subsequently, it gradually decreased to 5.67 mM approaching the normal range. In the case of TG, it was at a fasting level of 0.24 mM showing a similar value with the reported normal beagle's TG range 32 . TG further increased to 0.91 mM after the IV glucose injection and then decreased to 0.279 mM after 105 min due to the action of insulin.…”
Section: In Vivo Correlation Analysis Between Bg and Tg With Normal A...supporting
confidence: 86%
See 2 more Smart Citations
“…In addition, lipids (cholesterol, cholesteryl ester, phospholipids), small molecules (uric acid, ascorbic acid, lactate, glucose), electrolytes (sodium, potassium, calcium, magnesium) are contained in tears. Among these substances, several constituents have been found to correlate with blood levels and can serve as biomarkers for metabolic diseases. For instance, the correlation between blood and tear glucose levels has been studied, with tear glucose levels reflecting blood glucose levels with a time delay of around 10 min. Furthermore, Song et al conducted tests on rabbits that had been fed a cholesterol-rich chow diet, and the results of the tests revealed that cholesterol levels had increased for several weeks in both tears and blood, indicating that cholesterol in tears can be used as a biomarker to reflect blood cholesterol levels . These findings suggest that tears have the potential to serve as a noninvasive tool for personalized medicine and healthcare in the context of metabolic diseases.…”
Section: Manageable Diseases Through Eyesmentioning
confidence: 99%